An Overview of Islamic Dispute Resolution in the United States - Lee Ann Bambach; Yasemin Çelikhası (Darulfunun Ilahiyat)
This paper provides a comprehensive overview of Islamic dispute resolution practices in the United States, addressing the intersection of U.S. secular law and Islamic legal traditions. It begins with an examination of the U.S. Muslim population and explores how constitutional guarantees of religious freedom as well as the U.S. arbitration laws and the types of alternative dispute resolution (ADR) used in the United States have enabled religious communities to establish faithbased dispute resolution systems, such as Christian Conciliation and rabbinic tribunals, whose decisions are enforced by U.S. courts. The main focus of this paper is on Islamic dispute resolution traditions such as ṭaḥkīm and their practical application, describing the types of Islamic dispute resolution organizations that have been developed in the United States over the past few decades and how they function, aiming to provide insights into the evolving role of Islamic dispute resolution within the U.S. legal framework.